Analysis of Competitive Advantage Strategy at QU Laundry in Tuah Madani District, Pekanbaru City - Nadila Putri Atdika; Jushermi Jushermi; Agnes Alvionita; Prima Andreas (Westscience Press, 2025)
This study aims to analyze the competitive advantage strategy of QU Laundry in Tuah Madani District, Pekanbaru City. The increasing competition in the laundry business requires entrepreneurs to apply the right strategies to survive and grow. This research uses a descriptive method with a qualitative approach. Data were collected through interviews, observation, and documentation. Data analysis employed the SWOT matrix to identify strengths, weaknesses, opportunities, and threats, followed by the IFE and EFE matrices to determine the company’s strategic position. The results show that the total IFE score is 3.28 and the EFE score is 3.06, placing QU Laundry in the Grow and Build strategy position. Recommended strategies include improving promotion, utilizing digital technology in services, and developing innovations to strengthen competitiveness and expand market share in Pekanbaru City.